Integrasi Komik Digital Sebagai Media Visual Dalam Pengajaran Menulis Teks Eksposisi di Era Digital - Anita Candra Dewi (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstract: This study aims to analyze the effectiveness of using digital comics as a visual medium in teaching expository writing at the secondary school level. The research employed an experimental method with a quantitative approach. The sample consisted of two groups: an experimental group that utilized digital comics and a control group that followed conventional teaching methods. Data were collected through writing proficiency tests and questionnaires measuring students’ interest and learning motivation. The findings revealed a significant difference between the experimental and control groups. The average writing test score of the experimental group was higher (82.4) compared to the control group (68.3), with a t-test result indicating a p-value of 0.000. Additionally, the questionnaire showed that 85% of students in the experimental group reported higher interest in learning, in contrast to 58% in the control group. These results suggest that digital comics can enhance expository writing skills and student motivation. The use of digital comics helps students better understand the structure of expository texts through engaging and interactive visual elements. In addition to improving students’ writing quality, digital comics also make the learning process more enjoyable and flexible. Therefore, this study concludes that digital comics can serve as an effective and innovative learning medium to enhance expository writing skills in the digital era.